Determinants of Bilingualism among Children - Barry R. Chiswick; Marina Gindelsky (Institute for the Study of Labor (IZA), 2014)
This paper analyzes the determinants of bilingualism (i.e., speaks a language other than English at home) among children age 5 to 18 years in the American Community Survey, 2005-2011. Two groups of children are considered: those born in the US (native born) and foreign-born children who immigrated prior to age 14 (the 1.5 generation). The analyses are conducted overall, within genders, and within racial and ethnic groups. Bilingualism is more prevalent if the parents are foreign born, less proficient in English, of the same ancestry (linguistic) group, and if the child lives in an ethnic (linguistic) concentration area. Although the effects are relatively smaller, a foreign-born grandparent living in the household increases child bilingualism, while a higher level of parental education tends to decrease it. Children of Asian and especially of Hispanic origin are more likely to be bilingual than their white, non-Hispanic counterparts. Native-born Indigenous children are more likely to be bilingual.
Keywords: J15; J24; I21; Z13; 330; bilingualism; native born children; immigrant children; family